2021
DOI: 10.1186/s12903-021-02004-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between DMFT index and number of pregnancies: a cross-sectional study on enrollment phase of the Tabari Cohort Study

Abstract: Background People of all age and gender groups are at risk of dental diseases; however, some groups, such as pregnant women, are more vulnerable than others due to their specific physiological situations. The protection of maternal and fetal is critical. Therefore, the present study intended to investigate the relationship between the Decayed, Missing, and Filled Teeth (DMFT) index and the number of pregnancies. Methods The present cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In the present study, the findings of model 2 and model 3 showed that women with ≥4 pregnancies had higher DMFT than other women, which is in line with the findings of the study of Gorji et al (2021) in Mazandaran which showed that the average DMFT index in women increases with increasing number of pregnancies [ 4 ]. However, they did not assess the frequency of tooth brushing as a confounding factor in the analysis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the findings of model 2 and model 3 showed that women with ≥4 pregnancies had higher DMFT than other women, which is in line with the findings of the study of Gorji et al (2021) in Mazandaran which showed that the average DMFT index in women increases with increasing number of pregnancies [ 4 ]. However, they did not assess the frequency of tooth brushing as a confounding factor in the analysis.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between DMFT and age at first pregnancy is controversial. In the study of Gorji et al (2021) no significant relationship was reported between the age at first pregnancy and DMFT index [ 4 ]. This was consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental caries and gingivitis in pregnant occurred 1.97 times more frequently [ 6 ]. The mean DMFT index in women with 1, 2, 3, 4, 5, 6, and more than six pregnancies was obtained at 12.74 ± 7.11, 13.09 ± 7.06, 14.80 ± 7.81, 17.07 ± 8.11, 19.82 ± 9.02, 22.89 ± 8.98, and 26.17 ± 8.01, respectively, and the DMFT index increased by 34% for each unit increase in the number of pregnancies [ 7 ]. In Chinese pregnant women, the rates of tooth decay, periodontal health, mass detection, shallow periodontal pocket, deep periodontal pocket, regular oral examination, correct brushing, DMFT index, and caries filling ratio were 69.8%, 1.8%, 95.6%, 51.1%, 4.9%, 22.8%, 49.6%, 2.27%, and 45.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%